Dissimilarity Mesh Size Assessment for Two Dimensional Flood Routing Model - Azad W.H.; Mohd Sidek L.; Basri H.; Hassan A.J. (Springer, 2023)
2 Dimensional (2D) flow modeling is widely used for flood plain analysis and is considered to be a viable tool for evaluating flood propagation. The accuracy of open channel hydraulics and flood plain model is dependent on the refinement of model mesh or grid to represent ground model topography using high-resolution Light Detection and Ranging (LiDAR). This paper examines the sensitivity of unstructured mesh size of two dimensional (2D) shallow water models. The accuracy of simulated overland flood propagation was carried out using the Delaunay refinement method. The study was performed by connecting to the 2D hydrodynamic modeling platform InfoWorks Integrated Catchment Modelling (ICM) using two different methodologies. The first method is based on the generation Baseline of mesh model from the Digital Terrain Model (DTM), whereas the second method is based on the different mesh size. The results of flood propagation were analyzed using dissimilarity mesh resolutions in term of surge degree and run time. It can be concluded that the spatial resolution of the hydrodynamic model discretization influences model skill in simulating water surface elevation, flood depth, and agreement between inundation maps. However, further study is necessary to understand the entire performance of the two suggested methods. 2020, Springer Nature Singapore Pte Ltd.